PENGARUH STRUKTUR KEPEMILIKAN, KEBIJAKAN DIVIDEN, HUTANG DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN - Pertiwi, Santi Trisno; Hermanto, Suwardi Bambang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is meant to examine the influence of ownership structure which consists of managerial ownership (SKM) and institutional ownership (SKI), dividend policy (DPR), debt policy (DER), and profitability (ROE) to the firm value. The population of this study is all over of property companies in 2012-2015 periods which are listed in Indonesia Stock Exchange (IDX).The sample selection has been done by using purposive sampling to the 172 financial statements of 43 property companies which are listed in Indonesia Stock Exchange (IDX) and the data has been obtained from the official website of Indonesia Stock Exchange (www.idx.co.id). This test uses multiple linear regression analysis technique with SPSS (Statistical Product and Service Solutions) application tool. The result of the analysis which has been done by using multiple analysis shows that managerial ownership (SKM), dividend policy (DPR), debt policy (DER) and profitability (ROE) give positive influence to the firm value whereas institutional ownership (SKI) does not give any influence to the firm value with the Adjusted R Square is 0.234 or 23.4% That the independent variable is less able to influence the dependent variable while the remaining 0.766 or 76.6% is influenced by other variables.